Acquiring Core Investigative Interviewing Skills in Police Academy Training. (11th April 2021) - Mount, David; Mazerolle, Lorraine
Abstract: The ability of a police officer to elicit case-relevant information from a witness, victim, or suspect of a crime is a fundamental component of policing capability. The skills required to conduct an effective interview are not innate requiring police officers to be formally trained. The structural design, teaching, and assessment methods employed in the delivery of investigative interviewing training are assumed to directly impact a trainee's level of engagement and level of interviewing knowledge and skills acquired. This paper uses a qualitative case study approach to observe how core investigative interviewing skills are acquired through formal training. Our findings suggest a relationship between the adult learning construct adopted, the levels of learner engagement generated, and the achievement of desired learning outcomes. Our findings will inform future designs of investigative interviewing training that seek to maximize both learning outcomes and returns on resource investments.